To vaccinate or not Against Covid-19: A Cross Sectional Survey Among Dental Health Care Workers of Pakistan - Annam Imtiaz, Muhammad Hassan, Usman Yousaf, Aqsa Arif, Muhammad Sharif Khar, Ch. Rehan Qamar, Amina Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Therefore this study was conducted to assess the awareness status, acceptability and apprehensions associated with corona virus vaccine among dental health care practitioners. Method: The Multicenter cross sectional survey was conducted on 350 respondents from March 1st till March 31st 2021 based on non-probability consecutive sampling technique after confirming their eligibility. The sample size of 318 respondents was calculated. Binary logistic regression analysis was used to assess the determinants (Gender, Income level, Designation, History of self/family member for COVID-19 infection and Apprehensions) of vaccine acceptability. Results: Binary logistic regression analysis suggested 3.6 times more acceptance of COVID- 19 Vaccination in males compared to females (OR=3.594, 95% CI, 1.96-6.59, p<0.001), Participants who were not apprehended about the vaccination showed 5.75 times more acceptance (OR=5.745, 95% CI, 2.826-11.628, p <0.001), However being dental students showed negative prediction for the acceptance level (OR=0.172, 95% CI, 0.31-0.965, p value=0.045). Conclusion: In conclusion, findings of the Current study suggested low overall acceptance of COVID-19 Vaccination among dental healthcare workers (40.6%). The highest acceptance was found in Postgraduate residents (70.7%). The vaccine acceptance was greater in males (OR=3.594) and respondents who were not apprehended about the vaccine (OR=5.75).